The incidence and clinical ramifications for leadless pacemaker fixation mechanism exposure on the epicardial surface. (24th May 2021) - Breeman, KTN; Burke, MC; Shuros, A; Soltis, B; Brisben, A; Kilvington, J; Swackhamer, B; Knops, RE; Tjong, FVY
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Boston Scientific and Abbott Background: Leadless pacemaker (LP) fixation mechanism exposure (FE) by penetration of the epicardial surface has been described. Previously reported animal model studies showed FE for 7/10 Micra LPs, versus 4/10 CapSureFix Novus RV pacing leads (both Medtronic). However, it is unknown whether FE causes pericardial effusion or pericarditis or does not have clinical significance. Purpose: To determine the incidence of FE of a novel LP in a chronic animal model and its association with acute or chronic pericardial effusion. Methods: Canine subjects were implanted with novel LPs (Boston Scientific) in an ongoing study. Acute pericardial effusion was assessed by post-procedural transthoracic echocardiography (TTE). Chronic pericardial effusion was assessed by TTE 90 days after implantation and post-mortem assessed pericardial fluid colour (PFC) and volume (PFV). FE was assessed visually at necropsy. Mann-Whitney U tests and chi-squared tests were used to determine whether greater PFV, more haemorrhagic PFC or LP implantation location differed significantly between subjects with and without FE. Results: Results to date are reported. Canine subjects (n = 71) were chronically implanted with LPs. Due to 14 in-vivo retrievals, data is shown of 57 subjects with LPs in situ at necropsy. Pre-deployment radiocontrast injection confirmed LP position (RV apex n = 41; RV apicoseptal n = 16), and mechanical stability and electrical testing confirmed adequate talon fixation after deployment. Necropsy after median 94 days (IQR 91-540) demonstrated FE in 11 cases (19%) (figure). No acute nor chronic pericardial effusion was seen on TTE. Mean PFV for animals with and without FE was 1.8 and 1.6 cc, respectively. FE did not show an association with PFV or colour (p= 0.53 and p = 0.83, respectively). For two animals, PFV and PFC are not available; FE was not observed in either of these cases. LP implantation location was not associated with incidence of FE (p = 1.00). Conclusion: Fixation mechanism exposure by the talons of a novel leadless pacemaker was observed in 19% of animals implanted and was not associated with acute or chronic pericardial effusion.